2020
DOI: 10.1155/2020/2710907
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological Characterization of Kenyan Slender Leaf (Crotalaria brevidensandC. ochroleuca) Accessions

Abstract: Slender leaf (Crotalaria spp) is among the indigenous and underutilized vegetables in Kenya whose production is limited to the Western and Coastal regions of the country. For a long time, this crop has been neglected in terms of research and genetic improvement. There is therefore scanty information on its morphological diversity and agronomic performance, hence the need for this study. Field experiments were carried out for two seasons in October to December 2018 and March to May 2019. The experiments were la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
5
4
5
Order By: Relevance
“…Variability was observed in all the qualitative and quantitative traits investigated. Contrary to a previous study by Mwakha et al (2020), who reported lack of diversity in stem colour, dry pod colour, and hairiness of the stem. The study by Mwakha et al (2020), investigated two domesticated species hence the diversity could have been lost over time due to selection pressure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Variability was observed in all the qualitative and quantitative traits investigated. Contrary to a previous study by Mwakha et al (2020), who reported lack of diversity in stem colour, dry pod colour, and hairiness of the stem. The study by Mwakha et al (2020), investigated two domesticated species hence the diversity could have been lost over time due to selection pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to a previous study by Mwakha et al (2020), who reported lack of diversity in stem colour, dry pod colour, and hairiness of the stem. The study by Mwakha et al (2020), investigated two domesticated species hence the diversity could have been lost over time due to selection pressure. In agreement with the findings of Raj and Britto (2011), the present study established that most of the traits observed were not exclusive to a particular Crotalaria species with the leaf shape trait being among the most diverse qualitative trait.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to a previous study by Mwakha et al (2020), who reported lack of diversity in stem colour, dry pod colour, and hairiness of the stem. The study by Mwakha et al (2020), investigated two domesticated species hence the diversity could have been lost over time due to selection pressure. In agreement with the ndings of Raj & Britto (2011b), the present study established that most of the traits observed were not exclusive to a particular Crotalaria species with the leaf shape trait being among the most diverse qualitative trait.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the distinctiveness of this trait in most of the cultivated species was lacking, with observations of different lea et shapes in different plants of the same species. Overlap in leaf types in the species C. brevidens and C. ochroleuca which are common cultivated species in Kenya has been previously reported (Mwakha et al 2020). Therefore, this trait may not a good qualitative parameter for inheritance studies.…”
Section: Discussionmentioning
confidence: 97%